Genetic Linkage Mapping and Transmission Ratio Distortion in a Three-Generation Four-Founder Population of Panicum virgatum (L.). Issue 5 (1st May 2014) - Li, Guifen; Serba, Desalegn D; Saha, Malay C; Bouton, Joseph H; Lanzatella, Christina L; Tobias, Christian M
Abstract: Switchgrass ( Panicum virgatum L.), a warm season, C4, perennial grass, is one of the predominant grass species of the North American tall grass prairies. It is viewed as a high-potential bioenergy feedstock species because it can produce large amounts of lignocellulosic material with relatively few inputs. The objectives of this project were to develop an advanced switchgrass population and use it for the construction of genetic linkage maps and trait characterization. A three-generation, four-founder population was created and a total of 182 progeny of this advanced population were genotyped, including a mixture of self-pollinated and hybrid individuals. The female map integrated both subpopulations and covered 1629 cM of the switchgrass genome, with an average map length of 91 cM per linkage group. The male map of the hybrid progeny covered 1462 cM, with an average map length of 81 cM per linkage group. Average marker density of the female and male maps was 3.9 and 3.5 cM per marker interval, respectively. Based on the parental maps, the genome length of switchgrass was estimated to be 1776 cM and 1596 cM for the female map and male map, respectively. The proportion of the genome within 5 cM of a mapped locus was estimated to be 92% and 93% for the female map and male map, respectively. Thus, the linkage maps have covered most of the switchgrass genome. The assessment of marker transmission ratio distortion found that 26% of the genotyped markers were distorted from either 1:1 or 3:1 ratios expected for segregation of single dose markers in one or both parents, respectively. Several regions affected by transmission ratio distortion were found, with linkage groups Ib-m and VIIIa-f most affected.